Practical Aspects of Hair Transplantation in Asians (Springer Japan, 2018)
This book comprehensively discusses the practical aspects of hair transplantation in Asians. The demand for hair transplantation has increased globally in recent years and Follicular Unit Extraction (FUE) is gaining popularity. As such the book examines the techniques used by different ethnic group in Asia, included shaving, non-shaving FUE and robotic hair restoration surgery. With the help of illustrations, it describes surgical techniques and provides numerous practical tips. Written by leading experts and offering an overview of the current state of the art of hair restoration surgery, it enables experienced surgeons in the field to achieve optimal outcomes and to improve patients' QOL. It is a must read for hair surgeons performing hair transplantation on members of the Asian population.